Etos akademicki – historia i tradycja wobec wyzwań współczesności (próba rekapitulacji dyskusji) - Benenowska, Iwona (Acta Neophilologica, 2025)
The text is devoted to the academic ethos and aims to indicate the most important issues related to this problem. Individual thematic threads have been arranged and presented in the following order: 1. discussions and legal acts as well as publications devoted to the ethos from the end of the twentieth century to recent years; 2. history of the concept; 3. an attempt to find the essence of ethos and define it; 4. indication of certain types and categories of description of the ethos of science; 5. presentation of contemporary changes related to the globalization of science.